Protective Effect of Oxytocin on Ventilator-Induced Lung Injury Through NLRP3-Mediated Pathways - Yang, Xiaomei; An, Xiaona; Wang, Cheng; Gao, Feng; Lin, Yicheng; Chen, Wenjing; Deng, Qiming; Xu, Dongsheng; Li, Shengqiang; Zhang, Peng; Sun, Baozhu; Hou, Yuedong; et al. (Frontiers in Pharmacology, 2021)
Abstract Mechanical ventilation (MV) is an indispensable life-support treatment for acute respiratory failure in critically ill patients, which is generally believed to involve uncontrolled inflammatory responses. Oxytocin (OT) has been reported to be effective in animal models of acute lung injury. However, it is not clear whether OT has a protective effect on ventilator-induced lung injury (VILI). Therefore, in this study, we aimed to determine whether OT can attenuate VILI and explore the possible mechanism of this protection. To this end, a mouse VILI model was employed. Mice were pretreated with OT 30 min before the intraperitoneal injection of saline or nigericin and ventilation for 4 hours, after which they were euthanized. Pathological changes, lung wet/dry (W/D) weight ratio, myeloperoxidase (MPO) activity, the levels of inflammatory cytokines (i.e., interleukin (IL)-1β, IL-6, and IL-18) in lung tissues and bronchoalveolar lavage fluid (BALF), and expression of NLRP3, Toll-like receptor 4 (TLR4), caspase-1, nuclear factor (NF)-κB, and GSDMD in lung tissues were measured. OT treatment could reduce pathological injury, the W/D ratio, and MPO activity in VILI mice. Our data also indicated that OT administration alleviated the expression of TLR4/My-D88 and the activation of NF-κB, NLRP3, and caspase-1 in lung tissues from the VILI mice model. Furthermore, OT also decreased the levels of IL-1β, IL-6, and IL-18 in the BALF. Moreover, the OT administration may alleviate the activation of GSDMD partially through its effects on the NLRP3-mediated pathway. Collectively, OT exerted a beneficial effect on VILI by downregulating TLR4- and NLRP3-mediated inflammatory pathways.